2015
DOI: 10.1371/journal.pone.0118096
|View full text |Cite
|
Sign up to set email alerts
|

Plant Virus Particles Carrying Tumour Antigen Activate TLR7 and Induce High Levels of Protective Antibody

Abstract: Induction of potent antibody is the goal of many vaccines targeted against infections or cancer. Modern vaccine designs that use virus-like particles (VLP) have shown efficacy for prophylactic vaccination against virus-associated cancer in the clinic. Here we used plant viral particles (PVP), which are structurally analogous to VLP, coupled to a weak idiotypic (Id) tumour antigen, as a conjugate vaccine to induce antibody against a murine B-cell malignancy. The Id-PVP vaccine incorporates a natural adjuvant, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 52 publications
0
45
0
Order By: Relevance
“…Conjugation of the Id epitope to PVX through biotin-streptavidin interactions allowed for a multivalent presentation of the epitope. The multivalent display alongside with immune-stimulation through toll-like receptor-7 activation based on the encapsidated ssRNA genome of PVX led to enhanced immune stimulation, increased production of anti-Id antibodies, and improved resistance to Id-expressing BCL1 lymphoma challenge when compared to Id-streptavidin alone [44]. …”
Section: Immunotherapies and Vaccinesmentioning
confidence: 99%
“…Conjugation of the Id epitope to PVX through biotin-streptavidin interactions allowed for a multivalent presentation of the epitope. The multivalent display alongside with immune-stimulation through toll-like receptor-7 activation based on the encapsidated ssRNA genome of PVX led to enhanced immune stimulation, increased production of anti-Id antibodies, and improved resistance to Id-expressing BCL1 lymphoma challenge when compared to Id-streptavidin alone [44]. …”
Section: Immunotherapies and Vaccinesmentioning
confidence: 99%
“…PVX has been modified with the idiotypic (Id) immunoglobulin from B-cell lymphomas, a weak tumor antigen. When administered to mice, Id-PVX induced high titers of anti-Id antibodies, which prolonged survival after lymphoma challenge 69 .…”
Section: Vnp and Vlp Vaccines And Immunotherapiesmentioning
confidence: 99%
“…Immuno-based therapies tested in ovarian cancer include vaccines, immune checkpoint blockade and adoptive T cell therapy. [7][8][9] We previously showed that Cowpea mosaic virus (CPMV) can be used to generate VNPs (retaining the virus genomic RNA) or virus-like particles (VLPs) that lack the genomic RNA, and are thus termed empty CPMV (eCPMV) particles. [4] Although APCs are often present in both primary ovarian tumors and malignant ascites, including dendritic cells (DCs), tumor-associated macrophages (TAMs), tumor associated neutrophils (TANs), and myeloid progenitors, most of them have a pro-tumor, immunosuppressive phenotype.…”
Section: Introductionmentioning
confidence: 99%